2016
DOI: 10.4103/0974-2069.189117
|View full text |Cite
|
Sign up to set email alerts
|

Acquired fontan paradox in isolated right ventricular cardiomyopathy

Abstract: A 44-year-old woman presented with features of congestive heart failure. Echocardiography revealed severe right ventricular dysfunction along with passive minimally pulsatile pulmonary blood flow suggesting very high systemic venous pressures. This was confirmed with cardiac catheterization in which the pressures of superior vena cava and inferior vena cava (19 mmHg) were higher than the pulmonary artery pressures (17 mmHg). Elevation of systemic venous pressures above the pulmonary venous pressures, Fontan pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Such a result is somehow expected since in absence of any contractile ventricular activity the model reproduces the passive conduit behaviour in which the blood flows from RA into PuA. Thus, the nonfunctional RV leads to condition similar to the spontaneous evolution of the Fontan circulation, as highlighted in Saran et al 45 . However, in the simulated case, RA function is maintained and therefore RA effectively 'takes over' as the main right-sided pump.…”
Section: Discussionsupporting
confidence: 54%
“…Such a result is somehow expected since in absence of any contractile ventricular activity the model reproduces the passive conduit behaviour in which the blood flows from RA into PuA. Thus, the nonfunctional RV leads to condition similar to the spontaneous evolution of the Fontan circulation, as highlighted in Saran et al 45 . However, in the simulated case, RA function is maintained and therefore RA effectively 'takes over' as the main right-sided pump.…”
Section: Discussionsupporting
confidence: 54%
“…We also observed that, importantly, when the contractile activity is absent ( p = 100%), the model captures the nearly constant P rv and Q pv . Such a result, somehow expected, shows that in absence of any contractile activity the right ventricle behaves like a passive conduit i.e., a condition similar to the spontaneous evolution of the Fontan circulation appears 46 , but with the RA still contracting.…”
Section: Discussionsupporting
confidence: 53%
“…It is good to know that both nature and surgeons are revising the limitations of creating a Fontan circuit so that current limitation of age and pulmonary vascular resistance is revised to higher numbers. [ 3 4 ]…”
mentioning
confidence: 99%